Money Laundering: The Nature, Effects and Mechanism of Confrontation (Journal of Human Sciences, 2022)
Money laundering is one of the most serious crimes that threaten the economy and the most serious threat to security, political and social stability. Poses a real challenge to the competent authorities and financial institutions at the local and international levels, because it is related to the money that forms the backbone of the economy in the state, and this crime is linked to other crimes such as international terrorism. Given the seriousness of this crime, international efforts have combined and pushed countries to combat it through many international conventions, standards and rules in this field. In addition to the international efforts aimed at curbing this crime, there has been interest in combating crime at the local level, and most countries have adopted anti-money laundering legislation. On the Palestinian level, we note that the Palestinian National Authority has paid great attention to this issue, and has issued Decree Law No. (20) Of 2015 regarding combating money laundering and terrorist financing to confront this crime. This study aims to identify the concept of money laundering operations and its methods, and the stages it goes through, and the consequences thereof, whether from an economic, social, political or security point of view. With an explanation of the efforts of the international community in addressing this crime, which had a primary role in confronting this type of crime. The extent to which Palestinian legislation is compatible with international texts and efforts aimed at confronting this crime.